LAYANAN KONSELING BAGI ATLET PERSATUAN TENIS MEJA PADE ANGEN MATARAM 2020 - Aminullah Aminullah; Nurdin Nurdin (Abdi Masyarakat, 2020)
The background of the community service activity between the Program and the Tennis Association of the Psychology Study Program of UNDIKMA (Department of Sports and Counseling Guidance). these are as follows. In order to achieve optimal performance, athletes need not only to have excellent physical and technical abilities, but also psychological skills (psychological skills). This happens in badminton, which needs guidance from adolescence. The goal of counseling for athletes is to develop nine mental skills for athletes ranging from attitude to concentration. The method used is action research (action research) which includes focus group discussions, interviews, group counseling, observation of match situations to individual counseling. This activity involved technical trainers, physical trainers, teachers, boarders and male and female athletes aged 12-18 years from the single, men's and women's doubles and PB Pade Angen as well as lecturers and students of Psychology UNDIKMA (Department of Sports and Counseling Guidance). This collaboration is under the auspices of a Memorandum of Understanding between the two institutions under the auspices of PB Pade Angen Table Tennis. This activity during July - October 2020 resulted in a counseling program, 2 articles in the accredited electronic media Mandala Mataram Journal.